Investigation of Geotechnical Properties of Soil (Case Study: Amonunag Ini L.G.A. Akwa Ibom State) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This research work was carried out to determine the geotechnical properties of soil samples from Annanmong-Ebo road at Ini L.G.A., Akwa Ibom State. The investigation was carried out to ascertain the sub-soil conditions which were expected to support the proposed infrastructure. The brief of the investigation was carried out on six (6) samples bored to a depth of 1.0m below the existing ground level after top soil. Results and interpretations contained in this report were based on the six bored samples positioned within the site at CH 0 + 000, CH 0 + 500, CH 1 + 250, CH 1 + 900, CH 2 + 500 and CH 3 + 450. The Litho-stratigraphy of the site revealed moderately soft to moderately stiff light brownish sandy-clay lateritic soil from top down to 1.0m. Groundwater was not encountered during the boring, the critical laboratory results of the soil samples presented average value for moisture content of 18.5%; average liquid limit of 27%. The Unconfined compressive strength was 57KN/m2 and the shear strength was 28.5KN/m2. To support any proposed structure sited in this location, the results, analysis and interpretations of the tests as contained in this report will be found useful in designing the foundation of such infrastructure. Estimated settlement is expected within permissible limits.